Congenital hyperthyroidism: autopsy report - Lima,Marcus Aurelho de (1999)
We report the autopsy of a stillborn fetus with congenital hyperthyroidism born to a mother with untreated Graves' disease, whose cause of death was congestive heart failure. The major findings concerned the skull, thyroid, heart, and placenta. The cranial sutures were closed, with overlapping skull bones. The thyroid was increased in volume and had intense blood congestion. Histological examination showed hyperactive follicles. The heart was enlarged and softened, with dilated cavities and hemorrhagic suffusions in the epicardium. The placenta had infarctions that involved at least 20% of its surface, and the vessels of the umbilical cord were fully exposed due to a decrease in Wharton 's jelly. Hyperthyroidism was confirmed by the maternal clinical data, the fetal findings of exophthalmia, craniosynostosis, and goiter with signs of follicular hyperactivity. Craniosynostosis is caused by the anabolic action of thyroid hormones in bone formation during the initial stages of development. The delayed initiation of treatment in the present case contributed to the severity of fetal hyperthyroidism and consequent fetal death.